2003
DOI: 10.1108/08876040310467943
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of differential loci with perceived quality and behavioral intentions

Abstract: This paper suggests that he/she whom the customer holds most responsible for a service experience may influence which service quality dimensions take precedence in customer satisfaction, word‐of‐mouth intentions, and repurchase intentions. Results indicate that, when consumers find the contact employee more responsible for the experience, what is delivered is most important to evaluations of service quality, satisfaction, and behavioral intentions. When management is thought to be more responsible, how the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2009
2009
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 60 publications
0
31
0
3
Order By: Relevance
“…A number of researchers find complaint satisfaction influences repurchase intention (Strauss, 2002). The locus of causality, which refers to the individual or service attribute that led to the consumer complaint, influences consumer perceptions during the complaint and service recovery process (Swanson & Davis, 2003). Ang and Buttle (2006) find that a comprehensive service recovery process is positively associated with repurchase intention.…”
Section: Antecedents Of Repurchase Intention 275mentioning
confidence: 95%
“…A number of researchers find complaint satisfaction influences repurchase intention (Strauss, 2002). The locus of causality, which refers to the individual or service attribute that led to the consumer complaint, influences consumer perceptions during the complaint and service recovery process (Swanson & Davis, 2003). Ang and Buttle (2006) find that a comprehensive service recovery process is positively associated with repurchase intention.…”
Section: Antecedents Of Repurchase Intention 275mentioning
confidence: 95%
“…Further, the latest researches proved the 'gap theory' to be a relevant and effective tool for service management (Centeno et al 2008). The results of various researches (Grapentine 1998;Swanson, Davis 2003) show that reüabüity is the most important dimension for service users, whereas tangibles are the least important.…”
Section: Word Of Mouth Communicationsmentioning
confidence: 98%
“…Zeithaml et al (1996) found that favorable behavioral intentions are associated with a service provider's ability to get its consumers to: (1) say positive things about them; (2) express preference for their company; and (3) increase their purchase volume or agree to pay a price premium. Bendall-Lyon and Powers (2004) suggest that the outcome variables of "intention to return to the service provider" and "word-of-mouth communication" are two of the indicators most used for measuring behavioral intentions, which is generally supported in the literature (i.e., Babakus and Boller, 1992;Cronin and Taylor, 1992;Soderlund, 2006;Swanson and Davis, 2003).…”
Section: Behavioral Intentionsmentioning
confidence: 99%